1991
DOI: 10.12938/bifidus1982.10.1_19
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response of Bifidobacterium-Monoassociated Mice

Abstract: Various investigators have discussed floral microorganisms influence on a host's immune system (4, 6, 9). Most of these statements come from investigations comparing responses of germfree animals and flora-bearing ones. The present authors attempted to analyze the effect of an indigenous floral organisms on the host under a more simplified condition. Bifidobacterium longum (BL) was given per os to germfree mice (GF) of BALB/c background and various aspects of immune responses to the associated organism were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…Bifidobacterium is reported to enhance immunopotentiation by increasing IgA antibody production in vitro as well as in vivo by oral administration to germ-free mice (22)(23)(24)(25), and Rao (26) assumed that changes in intestinal microflora by dietary fibers affect the immunological functions .…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium is reported to enhance immunopotentiation by increasing IgA antibody production in vitro as well as in vivo by oral administration to germ-free mice (22)(23)(24)(25), and Rao (26) assumed that changes in intestinal microflora by dietary fibers affect the immunological functions .…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports on the effects of lactic acid bacteria concerning non-specific stimulation of the defense mechanism after oral administration [24]. Yamazaki et al [27] also reported that B. longum monoassociated mice exhibited beneficial effects with respect to specific and non-specific immunological defense reactions. However, Yamazaki et al [26] reported that antibacterial activity against E. coli administered into the stomach at a high dose was not observed in germ-free mice fed heat-killed B. longum.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that treatment with Bifidobacterium stimulates the nonspecific immune function [23,27], and Fujisawa et al [11] have reported that an administration of a culture condensate of Bifidobacterium longum (MB) increased the enzyme activity of intestinal epithelial cells and controlled the intestinal flora in rats.…”
mentioning
confidence: 99%
“…Conversely, if the possibility of causing sepsis or infection is high after probiotic translocation occurs, the probiotics should not be used even if it has low translocation ability. Yamazaki et al (1985Yamazaki et al ( , 1991 reported interesting investigations using germfree mice. When the pathogen E. coli O-111 was administered orally to germfree mice, most mice died within a few weeks because E. coli O-111 was translocated and produced enterotoxin in organs.…”
Section: Translocation Of Probiotics and Virulencementioning
confidence: 99%